Model and Technique of Stress Management: Strategies for Controlling Stress and Enhancing Daily Life (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Stress management refers to a widespectrum of techniques and psychotherapies aimed at controlling a person'slevels of stress, especially chronic stress, usually for the purpose ofimproving everyday functioning.